A Psycholinguistic Investigation of Cognitive Mechanisms in Employee Speech and Conversation Dynamics at an Automated Teller Machine Filling Office - Eka Melati; S Suryanti; Zaidun Naim; Ahmad Munawir; Imam Jayanto; Muh. Hasyim Rosyidi (CV. Media Digital Publikasi Indonesia, 2026)
This study explores the cognitive processes underlying employees’ utterances and conversational dynamics in the specific context of an ATM cash replenishment office from a psycholinguistic perspective. The study's goal is to discover how employees process, organize, and express linguistic information during high-pressure task-oriented interactions. This research adopts a qualitative design. The data consist of employees’ utterances produced in the ATM replenishment office. Data sources include four bank officers, twelve ATM technicians, and ten customers. Data were collected using the participant observation method (simak libat cakap), in which the researcher observed the dynamics and cognitive processes of bank officers’ and ATM employees’ speech through audio recording and note-taking techniques. In-depth interviews were also performed with bank officers, ATM employees, and customers. Following data collection, the analytical process included transcription, data reduction, classification, verification, tabulation, interpretation, and drawing conclusions. The study’s result shows that the employees’s turn taking process, repair prosedures, and utterrance production, has influenced by time constraints, institutional norms, and cognitive load. Furthermore, the study indicates how shared mental models and implicit coordination can help sustain efficiency and accuracy in professional interactions. These resukts broaden the application of psycholinguistic research to organizational communication, especially in financial organizations where precision and clarity are crucial. Aside from its theoretical contribution, this study has practical implications for improving communication training, reducing operational errors, and strengthening teamwork in high-stakes operational settings.